2019
DOI: 10.1016/j.bj.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated roles for glycans in regulating the inhibitory function of CD22 on B cells

Abstract: CD22 is an inhibitory B cell co-receptor that recognizes sialic acid-containing glycoconjugates as ligands. Interactions with its glycan ligands are key to regulating the ability of CD22 to modulate B cell function, the most widely explored of which is antagonizing B cell receptor (BCR) signaling. Most importantly, interactions of CD22 with ligands on the same cell (cis) control the organization of CD22 on the cell surface, which minimizes co-localization with the BCR. In contrast with the modest ability of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 118 publications
(165 reference statements)
1
16
0
Order By: Relevance
“…Mechanistically, we found that, in addition to the ITIM docking motifs in the cytoplasmic tail, the lectin-carbohydrate binding activity of CD22 also contributes to α 4 β 7 regulation, although the reduction of α 4 β 7 levels on B cells, and the inhibition of PP homing were less dramatic in the lectin mutant than with ITIM deficiency. On B cells, CD22 associates in cis with α2-6 Sia modified membrane proteins including CD22 itself and CD45: these cis-interactions can bring ITIMbound SHP-1 phosphatase in close proximity to target substrates, altering the phosphorylation state and function of associated molecules (Enterina et al, 2019;Meyer et al, 2018). Using a biotin-tyramide-based proximity labeling method (Alborzian Deh Sheikh et al, 2018) to label molecules in close proximity to CD22, we reproduced the finding that CD45 and CD22 are α2-6 Siadependent CD22 cis-ligands, but we did not detect interaction with α 4 β 7 (data not shown), suggesting either that, such interactions are transient (Collins et al, 2004) or that CD22 acts through intermediate signaling molecules to regulate α 4 β 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, we found that, in addition to the ITIM docking motifs in the cytoplasmic tail, the lectin-carbohydrate binding activity of CD22 also contributes to α 4 β 7 regulation, although the reduction of α 4 β 7 levels on B cells, and the inhibition of PP homing were less dramatic in the lectin mutant than with ITIM deficiency. On B cells, CD22 associates in cis with α2-6 Sia modified membrane proteins including CD22 itself and CD45: these cis-interactions can bring ITIMbound SHP-1 phosphatase in close proximity to target substrates, altering the phosphorylation state and function of associated molecules (Enterina et al, 2019;Meyer et al, 2018). Using a biotin-tyramide-based proximity labeling method (Alborzian Deh Sheikh et al, 2018) to label molecules in close proximity to CD22, we reproduced the finding that CD45 and CD22 are α2-6 Siadependent CD22 cis-ligands, but we did not detect interaction with α 4 β 7 (data not shown), suggesting either that, such interactions are transient (Collins et al, 2004) or that CD22 acts through intermediate signaling molecules to regulate α 4 β 7 .…”
Section: Discussionmentioning
confidence: 99%
“…CD22, also called Siglec 2, is expressed mainly by B-lymphocytes and functions to inhibit B-cell receptor signaling [ 107 , 108 ]. The rationale for the development of a CD22 recombinant immunotoxin was based on characteristics of both HCL and non-HCL hematologic malignancies.…”
Section: Development Of Anti-cd22 Recombinant Immunotoxins For Hcmentioning
confidence: 99%
“…During embryonic development, different waves of progenitors from various sites of origin give raise to different B cell progenies [3], while B cell maturation in turn is fine-tuned and controlled by different populations of T follicular cells [4]. CD22 binding to glycans ensures self-tolerance [5] and several subsets of B lymphocytes exert themselves immunosuppressive functions [6].…”
Section: Spotlight On Reviewsmentioning
confidence: 99%
“…Enterina et al. focus on one particular element in the arsenal of tools meant to keep them at bay, a co-receptor found on B cells named CD22, which antagonises BCR signalling [5]. Much conveniently, the patterns of cell surface glycosylation differ markedly between vertebrates and pathogens.…”
Section: Also In This Issuementioning
confidence: 99%